2022
DOI: 10.31234/osf.io/3h8fj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Positive Association of Education with the Trust in Science and Scientists is Weaker in Highly Corrupt Countries

Abstract: One of the most prominent correlates of trust in science and scientists is the education level, possibly because educated individuals have higher levels of science knowledge and thinking ability, suggesting that trusting science and scientists rely more on reflective thinking abilities. However, it is relatively more reasonable for highly educated individuals to suspect authority figures in highly corrupt countries. We tested this prediction in two nationally representative and probabilistic cross-cultural dat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Cultural differences in the relationship between conspiracy, paranormal beliefs, and free will can be linked to Türkiye's specific situation. In cultures with higher levels of corruption, such as Türkiye, conspiracy theories are more common due to their higher likelihood of occurrence (Alper, 2023), rendering educational attainment a less effective predictor of such beliefs (Alper, Yelbuz, Akkurt, & Yilmaz, 2024). Hence, in these settings, critical thinkers might not reject conspiracy theories as quickly as those in cultures with lower corruption levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural differences in the relationship between conspiracy, paranormal beliefs, and free will can be linked to Türkiye's specific situation. In cultures with higher levels of corruption, such as Türkiye, conspiracy theories are more common due to their higher likelihood of occurrence (Alper, 2023), rendering educational attainment a less effective predictor of such beliefs (Alper, Yelbuz, Akkurt, & Yilmaz, 2024). Hence, in these settings, critical thinkers might not reject conspiracy theories as quickly as those in cultures with lower corruption levels.…”
Section: Discussionmentioning
confidence: 99%
“…This difference can be attributed to supernatural beliefs incorporating additional motivational elements, such as the concept of an afterlife, which are absent in secular ideologies. The nonmaterial essence of fatalistic determinism might nullify the need for material evidence for beliefs, thereby paving the way for ESBs, which lack concrete, falsifiable evidence (Alper & Yilmaz, 2024;Douglas et al, 2017). Consistently, past research has shown that religious and spiritual beliefs (e.g., Alper et al, 2021;Rutjens et al, 2020;Yilmaz et al, 2018) are major drivers of ESBs.…”
Section: Potential Explanationsmentioning
confidence: 93%
“…Drawing on a sample of more than one-hundred thousand participants from various countries, the researchers found that the positive association between education and trust in science depends on social context. In particular, an association between education and trust in science and scientists was practically non-existent in highly corrupt countries (Alper et al, 2023). While other cognitive factors have not been extensively researched, a recent study by our research group tested the incremental value of cognitive reflectiveness (i.e.…”
Section: Factors Underlying Trust In Sciencementioning
confidence: 99%